Movement induced tremor in musicians and non-musicians reflects adaptive brain plasticity - Lee, André; Schoonderwaldt, Erwin; Chadde, Mareike; Altenmüller, Eckart (Frontiers in Psychology, 2014)
Evidence exists that motor dexterity is associated with a higher tremor amplitude of physiological tremor. Likewise, lower frequencies are associated with motor control. So far only case reports of a higher amplitude of physiological tremor in musicians exist. Moreover, no study has investigated lower frequencies during a finger movement task in musicians who can be regarded as a model of motor expertise. We developed a model and derived 3 hypotheses which we investigated in this study: 1) Tremor amplitude is higher in the range of physiological tremor and 2) higher for frequency ranges of dystonic tremor in musicians compared to non-musicians; 3) there is no difference in tremor amplitude at frequencies below 4Hz. We measured tremor during a finger flexion-extension movement in 19 musicians (age 26.5±8.2 years) and 24 age matched non-musicians (age 26.5±8.7). By using empirical mode decomposition in combination with a Hilbert transform we obtained the instantaneous frequency and amplitude, allowing to compare tremor amplitudes throughout the movement at various frequency ranges. We found a significantly higher tremor amplitude in musicians for physiological tremor and a tendency towards a higher amplitude during most of the movement in the frequency range of 4-8Hz , which however was not significant. No difference was found in the frequency range below 4Hz for the flexion and for almost the entire extension movement. Our results corroborate findings that the 8-12Hz oscillatory activity plays a role in motor dexterity. However, our results do not allow for the conclusion that tremor at the frequency range of 4-8Hz is related to either plasticity induced changes that are beneficial for motor skill development nor to maladaptive changes as e.g. focal dystonia.